That D----d Brownlow : Being a Saucy and Malicious Description of Fighting Parson William Gannaway Brownlow - Humphrey, Steve; Brownlow, William Gannaway (Appalachian State University, 1978)
This is a narrative on the famous 19th century Tennessee Methodist minister and newspaper editor, William Gannaway Brownlow, who launched the weekly Tennessee Whig newspaper with Mason R. Lyon in 1839 to support the Whig Party. An important historical figure in support of the Whig Party and the Union side of the Civil War in East Tennessee, Brownlow also served as Governor of and in the U.S. Senate for the state of Tennessee. This narrative tells the story of his character and influence during the turbulent 1800s.
English
Keywords: Biography: religious & spiritual; Biography & Autobiography; Religious